On Strong Coupled Coincidence Points of g-Couplings and an Application - Tawseef Rashid; Qamrul Haq Khan; Hassen Aydi (Journal of Function Spaces)
The purpose of this paper is to prove the existence and uniqueness of a strong coupled coincidence point of F:X×X→X and g:X→X, involving Banach and Chatterjea type g-couplings. We also give some examples and an application in support of the given concepts and our main results.